Legal Review of the Right to Religious Holiday Allowance (THR) for Online Motorcycle Taxi Partners - Ida Kurnia (Universitas Negeri Semarang, 2025)
Online motorcycle taxi drivers are categorized as partners in a partnership relationship with the application company, meaning they do not receive employment rights as regular workers do, including the Religious Holiday Allowance (THR). However, in practice, they work under a system that closely resembles an employment relationship, such as the presence of binding rules, sanctions, and specific targets. This disparity creates legal issues and highlights the need for a study on the protection of their rights. Therefore, this research is conducted to provide online motorcycle taxi drivers with an understanding of their rights and the legal actions they can take. The research method used in this study is normative juridical, which analyzes law as a norm or rule that applies in society. This study aims to examine the legal status of online motorcycle taxi partners in the context of labor law in Indonesia and encourage regulatory reform to make it fairer and more adaptable to the dynamics of work in the digital era